2017
DOI: 10.1177/1010428317706054
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA FOXCUT promotes proliferation and migration by targetingFOXC1in nasopharyngeal carcinoma

Abstract: Long noncoding RNAs play an important role in various biological processes, including tumorigenesis. FOXC1 (Forkhead box C1) is a member of the Forkhead box family of transcription factors and plays a crucial role in nasopharyngeal carcinoma. In this study, a novel long noncoding RNA (FOXCUT) located upstream of FOXC1 was investigated in 42 nasopharyngeal carcinoma patients. Our analysis revealed that the expression levels of FOXCUT and FOXC1 in nasopharyngeal carcinoma tissues were significantly higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
(38 reference statements)
2
32
0
Order By: Relevance
“…Recent studies have demonstrated that FOXC1 is highly expressed in various cancers, including NSCLC, and is postulated to be a marker of poor prognosis In the present study, we identified that high FOXC1 expression in NSCLC patients was more frequently associated with adverse clinical parameters and poor OS independent of other clinicopathological prognostic factors, including lymph node status in NSCLC patients. This result was consistent with the conclusion of the study of Cao et al, in which FOXC1 expression was found to be elevated in NSCLC tissues and negatively correlated with patient survival .…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies have demonstrated that FOXC1 is highly expressed in various cancers, including NSCLC, and is postulated to be a marker of poor prognosis In the present study, we identified that high FOXC1 expression in NSCLC patients was more frequently associated with adverse clinical parameters and poor OS independent of other clinicopathological prognostic factors, including lymph node status in NSCLC patients. This result was consistent with the conclusion of the study of Cao et al, in which FOXC1 expression was found to be elevated in NSCLC tissues and negatively correlated with patient survival .…”
Section: Discussionsupporting
confidence: 56%
“…The transcription factor FOXC1 is a key regulator of several biological processes and its abnormal expression was found associated to poor survival in various malignant tumors and in the epithelial to mesenchymal transition (EMT) process [24,49,50]. Recent studies showed that the FOXCUT-FOXC1 regulatory network is associated with tumorigenesis and cancer progression in esophageal squamous cell carcinoma (ESCC) [50], oral squamous cell carcinoma (OSCC) [51] and nasopharyngeal carcinoma (NPC) [52].…”
Section: Rna-directed Transcriptional Gene Regulation By Pancrnas In mentioning
confidence: 99%
“…9,10 Recently, increasing evidence has demonstrated that lncRNAs can mediate the progression of tumorigenesis and metastasis in a variety of cancers by dysregulating gene expression at the transcriptional, post-transcriptional or epigenetic level. 12 -14 For example, the expression of lncRNA ANRIL is significantly elevated in NPC tissues, which has been negatively associated with the overall survival of patients, and ANRIL silencing by specific shRNA can effectively inhibit the proliferation and tumorigenesis of NPC cells. 12 -14 For example, the expression of lncRNA ANRIL is significantly elevated in NPC tissues, which has been negatively associated with the overall survival of patients, and ANRIL silencing by specific shRNA can effectively inhibit the proliferation and tumorigenesis of NPC cells.…”
Section: Introductionmentioning
confidence: 99%
“…11 Aberrant expression of lncRNAs has also been involved in the initiation and progression of NPC, as reported by several previous studies. [12][13][14] For example, the expression of lncRNA ANRIL is significantly elevated in NPC tissues, which has been negatively associated with the overall survival of patients, and ANRIL silencing by specific shRNA can effectively inhibit the proliferation and tumorigenesis of NPC cells. 15 Another study by Li, et al 16 also demonstrated the dysregulation of ln-cRNAs, which markedly mediated the progression of NPC, because ln-cRNA-ROR largely promoted proliferation and metastasis through the suppression of the p53 signalling pathway.…”
Section: Introductionmentioning
confidence: 99%